2022
DOI: 10.1186/s12885-022-10435-4
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 expression clinically associated with mature dendritic cells infiltration and T cell immune response in colorectal cancer

Abstract: Background Galectin-9 is a member of the galectin family and has been reported to have a tumor-promoting or antitumor effect in response to the immune microenvironment. However, the immunomodulatory effect of galectin-9 in colorectal cancer (CRC) remains unclear. The antigen presentation and antitumor immune effects of galectin-9 in CRC were examined in this study. Methods The expression of galectin-9, dendritic cell markers (CD208 and CD1a), T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…anti-tumor immunity of colorectal cancer. [45] However, the role of galectin-9 in cancer immune may vary amongst different cancer types. Whether galectin-9 could regulate DC function in lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anti-tumor immunity of colorectal cancer. [45] However, the role of galectin-9 in cancer immune may vary amongst different cancer types. Whether galectin-9 could regulate DC function in lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] A recent study in colorectal cancer reported that the expression level of galectin‐9 positively correlated with infiltration of mature DCs and increased infiltration of CD8 + T cells, indicating the supportive role of galectin‐9 in anti‐tumor immunity of colorectal cancer. [ 45 ] However, the role of galectin‐9 in cancer immune may vary amongst different cancer types. Whether galectin‐9 could regulate DC function in lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%